2013
DOI: 10.1159/000355744
|View full text |Cite
|
Sign up to set email alerts
|

A Candidate Gene Approach to ANCA-Associated Vasculitis Reveals Links to the C3 and CTLA-4 Genes but not to the IL1-Ra And Fcγ-RIIa Genes

Abstract: Background/Aims: The aim of the study is to search for associations between Antineutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV) and polymorphisms in the genes of four key molecules possibly involved in different pathogenic pathways; complement C3, CTLA-4, Fcγ-RIIa and IL1-Ra. Patients and Methods: Patients with AAV (n=105) subgrouped as microscopic polyangiitis or granulomatosis with polyangiitis (Wegener's granulomatosis) and myeloperoxidase (MPO) or proteinase 3 (PR3) ANCA positive were comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…Similar results were obtained by Persson et al, where the incidence of the C3F allele was significantly higher in proteinase-3 (PR3)-ANCA positive patients compared to healthy controls. The authors assume the C3F allele may influence binding to the complement receptors and enhance the activation of neutrophils [56]. In another study, Manenti et al reported that ANCA-SV patients with depleted C3 concentrations were older at the diagnosis, had lower glomerular filtration rate and features of TMA on biopsy.…”
Section: Pauci-immune Gnmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results were obtained by Persson et al, where the incidence of the C3F allele was significantly higher in proteinase-3 (PR3)-ANCA positive patients compared to healthy controls. The authors assume the C3F allele may influence binding to the complement receptors and enhance the activation of neutrophils [56]. In another study, Manenti et al reported that ANCA-SV patients with depleted C3 concentrations were older at the diagnosis, had lower glomerular filtration rate and features of TMA on biopsy.…”
Section: Pauci-immune Gnmentioning
confidence: 99%
“…Carries of C3F allele are at risk for the development of age-related macular degeneration (AMD) [46], partial lipodystrophy (PD) [51], and various types of GN: membranoproliferative glomerulonephritis type II (MPGN II, presently known as dense deposit disease, DDD) [51,52], IgA nephropathy (IgAN) [53,54] and systemic vasculitis (SV) [55,56]. Surprisingly, C3F allele has been shown to have a protective effect on transplant kidney, and its presence in donor's kidney may prolong the graft survival [57].…”
Section: The Genetic Background Of the Ap Abnormalities In Glomerularmentioning
confidence: 99%
“…Since then, a number of studies [41,42] have convincingly shown that activation of the alternative pathway of complement and an intact C5a receptor (C5aR) are necessary for the development of glomerulonephritis in murine models of vasculitis, prompting a re-assessment of the role of complement in human AAV. Moreover, C3F, a common coding genetic variant of C3, was found to be overrepresented in patients with AAV in small candidate gene studies [44][45][46]. Moreover, C3F, a common coding genetic variant of C3, was found to be overrepresented in patients with AAV in small candidate gene studies [44][45][46].…”
Section: Complementmentioning
confidence: 99%
“…Previous smaller genetic studies have shown alterations for AAV patients also in the genes PTPN22 (also reported in other autoimmune diseases), C3 (central component in the complement system), the IL 2 receptor (or CD25, expressed on activated cells and important for B and T cell survival), FcR (involved in phagocytosis and binds antibodies such as ANCA), CTLA4 (contact-inhibition of immunological responses) and IL-10 (antiinflammatory cytokine that dampens immunological responses) (Persson et al 1999, Willcocks et al 2010, Persson et al 2013). These genes did not reach statistical significance in the two GWAS studies but could still be important in AAV.…”
Section: Genetic Risk Factorsmentioning
confidence: 94%
“…AAV is considered pauci-immune, with only few immune complex depositions. However, many studies have shown the complement factor C3 to be deposited in glomeruli of patients , and patients possess an aberrant expression of the C3 gene (Persson et al 2013). Both C3a and C5a, which is important for neutrophil recruitment, appear to be increased in plasma and urine samples of active patients.…”
Section: Neutrophil Recruitmentmentioning
confidence: 99%